Attitudes of physical education teachers towards the inclusion of students with disabilities in the schools of the normal - Alkhudhari, Sultan (Journal of Physical Education, 2023)
The research aims to identify the attitudes of physical education teachers towards integrating students with disabilities in the schools of normal students, the differences between the attitudes of physical education teachers according to the variables (gender, academic qualification, years of experience, teaching stage), the researcher used the descriptive approach, the research sample was chosen in an intentional way from Physical education teachers in the General Administration of Education in Makkah Al-Mukarramah region , The researcher concluded that physical education teachers have a good level on the scale of physical education teachers’ attitudes towards integrating students with disabilities in the schools of the normal students, and there are statistically significant differences between males and females in the research sample in the axis of cognitive attitudes in favor of males, and the axis of emotional attitudes in favor of females, also there are statistically significant differences between the academic qualifications of the research sample in the axis of cognitive attitudes in favor of holders of master’s qualifications, and the axis of behavioral attitudes in favor of holders of PHD qualifications. There are also statistically significant differences between the years of experience of the research sample in the axis of cognitive attitudes in favor of years of experience from 5 to 10 years, and the axis of emotional attitudes in favor of years of experience less than 5 years. the list of criteria, and one of the most important results of the research is to extract a list of the proposed criteria to increase the demand among the elderly to participate in strength training programs, which included (7) axes, and (90).